The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/ncomms9899
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of TARBP2 regulates miRNA/siRNA efficiency

Abstract: Small RNA-induced gene silencing is essential for post-transcriptional regulation of gene expression; however, it remains unclear how miRNA/siRNA efficiency is regulated. Here we show that TARBP2 is SUMOylated at K52, which can be enhanced by its phosphorylation. This modification can stabilize TARBP2 via repressing its K48-linked ubiquitination. We find that TARBP2 SUMOylation does not influence the overall production of mature miRNAs, but it regulates miRNA/siRNA efficiency. SUMOylated TARBP2 recruits Ago2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 71 publications
0
46
0
Order By: Relevance
“…Thus, we focused on SUMO1 modification of METTL3 in the following studies. Since Sentrin/SUMO-specific protease 1 (Senp1) is an SUMO1 modification-specific protease (19), we wondered whether Senp1 can remove the SUMO1 modification. Indeed, the significantly increased SUMOylation of exogenous METTL3 by Ubc9 was greatly weakened by cotransfection of the plasmid Senp1 (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we focused on SUMO1 modification of METTL3 in the following studies. Since Sentrin/SUMO-specific protease 1 (Senp1) is an SUMO1 modification-specific protease (19), we wondered whether Senp1 can remove the SUMO1 modification. Indeed, the significantly increased SUMOylation of exogenous METTL3 by Ubc9 was greatly weakened by cotransfection of the plasmid Senp1 (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…It is becoming increasingly clear that SUMO modification plays important roles in the development and progression of cancer (19–21,26–28,48–50). Growing evidences have also revealed that key enzymes for m 6 A demethylation such as ALKBH5 (8,39) and FTO (38) have important regulatory roles in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the E3 ligase of TARBP2 and ubiquitination levels need to be determined for further investigation in cancer. Supporting this concept, the SUMOylation of TARBP2 stabilizes TARBP2 protein expression through reducing its ubiquitination to suppress tumor progression, indicating that the ubiquitination of TARBP2 is essential for cancer progression (Chen et al ., ). Additionally, autophagy facilitates sorafenib resistance in HCC cells (Liu et al ., ; Zhai et al ., ), suggesting that inhibition of autophagy resensitizes HCC cells to sorafenib treatment through blocking the degradation of TARBP2.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that AGO2 plays a key role in the RNA interference pathway and that other RNA modulators, such as TARBP2, may affect this and other pathways [49,50]. Thus the use of the AGO2 immunoblot alone was not sufficient in our study to gain a real measure of RNAi processing.…”
Section: Discussionmentioning
confidence: 85%